2011
DOI: 10.1007/s10753-011-9364-y
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Radon Inhalation on Carrageenan-Induced Inflammatory Paw Edema in Mice

Abstract: We assessed whether radon inhalation inhibited carrageenan-induced inflammation in mice.Carrageenan (1% v/v) was injected subcutaneously into paws of mice that had or had not inhaled approximately 2000 Bq/m 3 of radon for 24 hr. Radon inhalation significantly increased superoxide dismutase (SOD) and catalase activity and significantly decreased lipid peroxide levels in mouse paws, indicating that radon inhalation activate antioxidative functions. Carrageenan administration induced paw edema and significantly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 23 publications
0
33
0
Order By: Relevance
“…At 6 h after the last dose of CHU treatment, 50 lL of carrageenan dissolved in 0.9% saline (1% m/v) was injected into the right hind paw of rats. 19 Paw swelling volumes were measured at 30, 60, and 120 min after carrageenan administration. After the measurements of swelling volumes, the homogenates of right hind paw were used for immunoblotting.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…At 6 h after the last dose of CHU treatment, 50 lL of carrageenan dissolved in 0.9% saline (1% m/v) was injected into the right hind paw of rats. 19 Paw swelling volumes were measured at 30, 60, and 120 min after carrageenan administration. After the measurements of swelling volumes, the homogenates of right hind paw were used for immunoblotting.…”
Section: Animal Treatmentmentioning
confidence: 99%
“…In addition, a large number of patients are treated in various countries with traditional spa therapy (Japan [14–16], central Europe [17]). To assess the effects of radon, we have developed a radon-exposure system for small animals; using this system, we demonstrated that radon inhalation has anti-inflammatory effects and inhibits carrageenan-induced inflammatory paw edema [18]. We also demonstrated that radon inhalation inhibits the oxidative damage associated with CCl 4 -induced hepatopathy in mice, indicating that radon inhalation has anti-oxidative effects [19].…”
Section: Introductionmentioning
confidence: 99%
“…For example, radon inhalation activates antioxidative functions in many organs of mice and inhibits CCl 4 -induced liver and renal damage [18, 32, 33], type-1 diabetes [8], and pain [8, 34]. Interestingly, the absorbed dose of radon is much lower than X-irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in the search for new indications for radon therapy, we reported the responsiveness to radon of an antioxidant enzyme (a radical scavenger), superoxide dismutase (SOD), in mouse organs [7], and suggested that radon inhalation activated antioxidative functions in many organs of mice. In addition, it was demonstrated that radon inhalation has anti-inflammatory effects and inhibits carrageenan-induced inflammatory paw edema [8]. Furthermore, a clinical study was conducted using thoron, which is an isotope of radon.…”
Section: Introductionmentioning
confidence: 99%